Randomized clinical trial of oral and intravenous versus intravenous antibiotic prophylaxis for laparoscopic colorectal resection. Issue 12 (23rd August 2016) - Ikeda, A.; Konishi, T.; Ueno, M.; Fukunaga, Y.; Nagayama, S.; Fujimoto, Y.; Akiyoshi, T.; Yamaguchi, T.
Abstract: Background: The use of oral prophylactic antibiotics for the prevention of surgical‐site infection (SSI) in patients undergoing laparoscopic surgery for colorectal cancer is controversial. The aim of this RCT was to evaluate whether intravenous perioperative antibiotics are inferior to combined preoperative oral and perioperative intravenous antibiotics in this setting. Methods: Patients undergoing elective laparoscopic colorectal resection in a single cancer centre were assigned randomly to combined preoperative oral antibiotics (metronidazole and kanamycin) and perioperative intravenous antibiotics (cefmetazole) (oral/IV group) or to perioperative intravenous antibiotics (cefmetazole) alone (IV‐only group). Patients were stratified for the analyses based on type of operation (colonic surgery, anterior resection or abdominoperineal resection), preoperative use of mechanical bowel preparation, preoperative chemoradiotherapy and the presence of diabetes mellitus. The primary endpoint was the overall rate of SSI. Secondary endpoints were the rates of incisional site infection, organ/space infection, anastomotic leakage, intra‐abdominal abscess, adverse events and postoperative complications. Results: Of 540 patients offered participation in the trial in 2013–2014, 515 agreed to take part and were randomized. Some 256 patients in the IV‐only group and 255 in the oral/IV group completed the treatment per protocol. The overall rate of SSI was 7·8 per cent (20 of 256) in the IV‐only group and 7·8 per cent (20 of 255) in the oral/IV group, confirming that perioperative administration of intravenous antibiotics alone was not inferior to the combined regimen ( P = 0·017). There were no differences in rates of incisional site infection (5·5 versus 5·9 per cent respectively), organ/space infection (2·3 versus 2·0 per cent) or other secondary endpoints between the two groups. Conclusion: Intravenous perioperative antimicrobial prophylaxis alone is not inferior to combined preoperative oral and intravenous perioperative prophylaxis with regard to SSI in patients with colorectal cancer undergoing elective laparoscopic resection. Registration number: UMIN000019339 (http://www.umin.ac.jp/ctr/ ). Abstract : Non‐inferiority confirmed